Analysis of the marketing strategy of savings products at BMT Nasuha during the Covid-19 pandemic - Linda Nur Fitriyani; Tati Handayani; Lili Puspita Sari (Goodwood Publishing, 2025)
Purpose: This study aims to investigate the marketing strategies that can be applied by BMT Nasuha in marketing their savings products during the covid-19 pandemic. Research Methodology: This study uses descriptive qualitative research with a case study approach which is carried out by using observation, interviews, literature studies, and documentation techniques. Results: The results of the study show that the promotions are carried out by BMT Nasuha through social media, such as Instagram, Facebook, and Website. Before the covid-19 pandemic, BMT Nasuha did its marketing activities through recitation or training. The results of the SWOT analysis of BMT Nasuha show the position of quadrant 1, so that BMT Nasuha can take advantage of its internal strengths, namely developing a stable software system to support BMT operations and increase its human resources in achieving increased business growth. Conclusion: BMT Nasuha should pursue a growth-oriented strategy that exploits internal strengths to capture external opportunities, strengthening liquidity, outreach, and service quality. Limitations: In this study, it was difficult to give a SWOT questionnaire directly to several research subjects because they had other jobs besides their jobs in BMT Nasuha. So, it could only be entrusted to one of the staff. Contribution: It is hoped that this research can provide benefits to BMTs throughout Indonesia regarding marketing their savings products, especially for BMTs which are still relatively small.